Conceptualizing Conviviality in Urban Landscapes - Maria Beltran Rodriguez; Madlen Simon (Athens Journal of Architecture, 2015)
The research described in this paper is part of an ongoing investigation on the relationship between design solutions and the level of conviviality among users of urban landscapes, particularly within the context of areas characterized by a diverse population. This specific paper summarizes a literature review conducted on conviviality and explains the findings gathered when theoretical concepts were tested in a real environment, Superkilen park, as part of a pilot study conducted in 2015. Three broad branches are identified in the literature as necessary conditions for convivial environments: physical spaces that are flexible, changing and adaptable; processes and outcomes based in equity, integrity and democracy; and urban uses and solutions that correspond to people’s needs and desires. These three conditions have been translated into three equivalent design qualities of urban landscapes that can be objectively observed: flexible, inclusive and useful. The design elements and parts of Superkilen that shared any of these attributes were documented and mapped. These first findings indicate that certain design attributes can have an effect on the conviviality performance of an urban landscape. A better understanding of the relationship between design and user´s conviviality can inform architects, landscape architects, urban designers and planners on how to improve the public realm at the scale of the street, the neighborhood and the city.